1999
DOI: 10.1103/physrevlett.82.968
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Initial-Stage Oxidation Products on Si(111)-(7×7)

Abstract: Density functional theory calculations are used to study the initial-stage adsorption of O 2 molecules on the Si͑111͒-͑7 3 7͒ surface. Contrary to experimental suggestions, we find no evidence of metastable O 2 molecular states on this surface, i.e., O 2 molecules dissociate spontaneously without any barrier. Our electronic and vibrational analysis reveals that the resulting atomic-oxygen products can explain the "molecular" features reported in previous experiments. [ S0031-9007(99) PACS numbers: 68.35.Bs, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 27 publications
7
59
0
Order By: Relevance
“…In studies based on density-functional theory ͑DFT͒ calculations, 1,2 it was stated that the metastable oxygen has an atomic oxygen configuration. These DFT calculations 1,2 reinterpreted the earlier spectroscopic [3][4][5][6][7][8][9][10] and microscopic [11][12][13][14][15][16] results in which the metastable oxygen was reported to be a molecular species, a so-called molecular precursor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies based on density-functional theory ͑DFT͒ calculations, 1,2 it was stated that the metastable oxygen has an atomic oxygen configuration. These DFT calculations 1,2 reinterpreted the earlier spectroscopic [3][4][5][6][7][8][9][10] and microscopic [11][12][13][14][15][16] results in which the metastable oxygen was reported to be a molecular species, a so-called molecular precursor.…”
mentioning
confidence: 99%
“…These recent studies 18 -21 reported that the metastable molecular species adsorb on a Si͑111͒ surface, on which oxygen atoms are already adsorbed, and they showed the necessity to consider at least three oxygen atoms with different chemical environments. This number is different from that used for the previous models, i.e., only two oxygen atoms with different chemical environments have been considered for the atomic configuration 1,2,17 and the molecular precursor. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] This obvious conflict calls for an urgent and careful reinvestigation of the structural model of the metastable species, which is essential for the understanding of the oxidation process of Si on an atomic level.…”
mentioning
confidence: 99%
“…The structural similarity of the S B -O2b structure and the oxidation product of the adatoms on Si͑111͒-7 ϫ 7 looks quite reasonable. 47 Further inspection of the atomic geometry of the clean vicinal Si͑001͒ surface showed that the rebonds at the S B step are significantly elongated compared to the atomic bonds in bulk Si as much as 0.2 Å. As such, the RSAs become more flexible with respect to oxygen-induced strains.…”
Section: Discussionmentioning
confidence: 98%
“…The lifetime obtained in the valence-band studies might therefore be overestimated. In fact, although the 3.8 eV peak observed in the valence-band spectra was assigned to the * orbital of a molecular "paul" species in the early valence-band studies [5][6][7][8]10,11 and theoretical investigations, 3,21 recent valence-band 12 and theoretical 22,23 studies suggest that the origin is the p z orbital of an "ad" oxygen atom. The ad denotes an O atom bonding on top of a Si adatom of the dimer-adatom-stacking fault structure 25 of the Si͑111͒-͑7 ϫ 7͒ surface (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This metastable species, which has a finite lifetime and disappears after annealing the sample at 600 K, was observed in various spectroscopic [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and microscopic studies, [17][18][19][20] and it has also been treated theoretically. 3,[21][22][23][24] Despite these extensive research efforts, a complete picture of the processes determining the lifetime has not yet been obtained.…”
Section: Introductionmentioning
confidence: 99%